2014
DOI: 10.1016/j.yqres.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental change and seasonal behavior of mastodons in the Great Lakes region inferred from stable isotope analysis

Abstract: We investigate seasonal variations in the diet and drinking water of four Great Lakes mastodon (Mammut americanum) specimens using stable isotope analysis of serially sampled inner-enamel bioapatite structural carbonate (δ 13 C sc , δ 18 O sc ), and previously published bulk analyses. Isotopic analyses and thin section measurements showed that mastodon tooth enamel extension rates (~12-4 mm/yr, decreasing toward the cervix) were lower than those of mammoths or modern elephants. Mastodons had distinct and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 93 publications
(175 reference statements)
0
13
0
Order By: Relevance
“…Recent research supports the idea that the environmental niches of various proboscidean taxa were broader than traditionally envisaged (Saunders et al ., ; Metcalfe and Longstaffe, ; Baumann and Crowley, ). The example of AB12 (P96.12.1) demonstrates that mammoths in Alberta occupied a range of environments, and suggests that taxonomic designations based on stable isotope analyses should ideally be attempted for specimens from known locations and time periods, where baseline isotopic compositions for the taxa in question have already been determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research supports the idea that the environmental niches of various proboscidean taxa were broader than traditionally envisaged (Saunders et al ., ; Metcalfe and Longstaffe, ; Baumann and Crowley, ). The example of AB12 (P96.12.1) demonstrates that mammoths in Alberta occupied a range of environments, and suggests that taxonomic designations based on stable isotope analyses should ideally be attempted for specimens from known locations and time periods, where baseline isotopic compositions for the taxa in question have already been determined.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize bias, we sampled pieces of enamel that represented the entire enamel thickness (∼1–2 mm) and typically ∼10 mm or greater of tooth height, homogenizing the samples for each individual. Growth rate estimates for both mammoth and mastodon molar enamel indicate that more than 1 year is required for the full thickness of the enamel to develop (Metcalfe and Longstaffe, , ). Growth in the occlusal–basal direction of mammoth and modern elephant teeth occurs at a rate of 13–22 mm a −1 , with the faster rates only occurring near the occlusal surface (Dirks et al ., ; Metcalfe and Longstaffe, ; Uno et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…And yet, as studies in historic biogeography have shown, "understanding the structure of assemblages of species requires that the history of each species in that assemblage be studied on its own" (Grayson 2007, p. 194). That means developing highresolution records of the "biogeographic histories of individual species in relation to paleoclimatic, paleoecological, and archaeological data" (Faith 2014a, p. 5,434) that lead up to the times of extinctions so as to show how changes on the landscape-possibly including the arrival of humansmight have affected them (Grayson & Meltzer 2015, Lorenzen et al 2011, Meltzer 2009, Metcalfe & Longstaffe 2014, Orlando & Cooper 2014.…”
Section: Getting Past the Impassementioning
confidence: 99%